Subduction Zone Dynamics and Forearc Tectonostratigraphic Evolution: Talara Basin, northwestern Peru - Lajo Yáñez, Jorge Aníbal (2022)
Forearc basins are important archives for understanding the tectonic evolution of the plate margin and subduction zone through deep time because they preserve a tectonostratigraphic record of temporal and spatial interactions of eustasy, sediment supply, climate, basin physiography and tectonism. However, forearc basins have received less attention than rift and foreland basins, due to the limited number of exposed examples and classification traditionally restricted to accretionary margins. The Talara Basin in the northern Peruvian forearc, where the oceanic Nazca plate is being subducted beneath the continental South American plate, is a well-known example of a subduction-erosion margin, where the edge of the continental plate is consumed over time and accretionary processes play a minor role. From the Late Cretaceous to the Eocene, stratigraphic units from deep water to fluvial environments comprise a 9 km-thick basin fill that has been episodically deformed by extensional faulting due to forearc vertical movements produced by subduction. This work aims to characterise the spatial and temporal behaviour of subduction and how these processes are recorded in and affect the evolution of the forearc basin. The sequence stratigraphic approach is based on the integration of outcrop, well and seismic data sets. Sedimentology and analysis of stratal stacking patterns and key stratigraphic surfaces, integrated with tectonic studies show that the Eocene PariÃ Â±as Formation comprises three depositional sequences of fluvio-deltaic deposits that form a highstand sequence set. The succession is capped by a previously unrecognised composite sequence boundary marked by a regional palaeosol and overlain by the transgressive sequence set of the Chacra Formation. The composite sequence boundary may indicate the presence of a lowstand sequence set offshore. This integrated PhD project identified tectonically-enhanced/driven regressions and transgressions through the Eocene. Down-dip and across-strike system asymmetry was a response to uplift and extensional collapse events related to periods of locking and release of the subduction interface. These observations highlight the importance of a close temporal and spatial relationship between plate boundary and basin - a relationship unique to forearc basins, with worldwide application.